Impact of outsourced agricultural extension program on smallholder farmers' net farm income in Msinga, KwaZulu-Natal, South Africa. (May 2019) - Baiyegunhi, L.J.S.; Majokweni, Z.P.; Ferrer, S.R.D.
Abstract: This paper examines the determinants of participation in an outsourced extension programs and its impact of smallholder farmers' net farm income in Msinga, KwaZulu-Natal, South Africa. A multi-stage sampling technique was used to obtain cross-sectional farm-level data from a sample of 300 farm households, using a structured questionnaire for the interview. The determinants and impacts of participation were estimated using the propensity score matching (PSM) to account for sample selection bias. The results show that participation in an outsourced extension program is influenced by age, education, membership of a farmers' group, and off-farm income, farm size, awareness, trust and participation incentives. Participation in an outsourced extension program was found to have significantly contributed to an increase in net farm income of the participants by about R2700. Policy implications for scaling up outsourced extension service delivery are discussed. Highlights: This study estimated the impact of outsourced extension program on net farm income. It employed the Propensity Score Matching technique to correct for selection bias. Participation in outsourced extension program is influenced by socio-economic and institutional variables. Participants would have earned R2700 less in net farm income had they not participated in the extension program. Impact of participation in extension program also varies among participants.